Convenient Auto-Processing Vector Based on Bamboo Mosaic Virus for Presentation of Antigens Through Enzymatic Coupling - Yang, Ming-Hao; Hu, Chung-Chi; Wong, Chi-Hzeng; Liang, Jian-Jong; Ko, Hui-Ying; He, Meng-Hsun; Lin, Yi-Ling; Lin, Na-Sheng; Hsu, Yau-Heiu (Frontiers in Immunology, 2021)
We have developed a new binary epitope-presenting CVP platform based on Bamboo mosaic virus (BaMV) by using the sortase A (SrtA)-mediated ligation technology. The reconstructed BaMV genome harbors two modifications: 1) a coat protein (CP) with N-terminal extension of the Tobacco etch virus (TEV) protease recognition site plus 4 extra glycine (G) residues as the SrtA acceptor; and 2) a TEV protease coding region replacing that of the triple-gene-block proteins. Inoculation of such construct, pKB5G, on Nicotiana benthamiana resulted in the efficient production of filamentous CVPs ready for SrtA-mediated ligation with desired proteins. The second part of the binary platform includes an expression vector for the bacterial production of donor proteins. We demonstrated the applicability of the platform by using the recombinant envelope protein domain III (rEDIII) of Japanese encephalitis virus (JEV) as the antigen. Up to 40% of the BaMV CP subunits in each CVP were loaded with rEDIII proteins in 1 min. The rEDIII-presenting BaMV CVPs (BJLPET5G) could be purified using affinity chromatography. Immunization assays confirmed that BJLPET5G could induce the production of neutralizing antibodies against JEV infections. The binary platform could be adapted as a useful alternative for the development and mass production of vaccine candidates.